1999
DOI: 10.1034/j.1399-3011.1999.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an acid proteinase from mesophilic Mucor sp. solid‐state cultures

Abstract: The fourth-day extract of a solid-state culture of the mesophilic Mucor sp. (M-105) strain showed a high milk-clotting activity and a clotting/proteolytic activity ratio similar to that of commercial preparations from microbial origin used in cheese manufacture. After ultrafiltration of the crude extract, the milk-clotting proteinase was purified in two steps: ion-exchange followed by size-exclusion chromatography. Enzyme homogeneity was assessed by HPLC, SDS-PAGE and N-terminal residue determination. A pI val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…An overall purification factor of 15.5 and total enzyme yield of 46% were achieved, fitting very well with the standard procedures found in the literature. A similar strategy was also applied in the recovery and purification of the aspartic proteinase from M. circinelloides where a final yield of 76.2% and specific activity (purified enzyme) of 1,280 U/mg was obtained (Fernandez-Lahore et al 1999). Table 3 summarizes reports on the purification strategies of aspartic proteinases from Mucorales.…”
Section: Recovery and Purification Of Mucor Spp Aspartic Proteinasesmentioning
confidence: 99%
See 3 more Smart Citations
“…An overall purification factor of 15.5 and total enzyme yield of 46% were achieved, fitting very well with the standard procedures found in the literature. A similar strategy was also applied in the recovery and purification of the aspartic proteinase from M. circinelloides where a final yield of 76.2% and specific activity (purified enzyme) of 1,280 U/mg was obtained (Fernandez-Lahore et al 1999). Table 3 summarizes reports on the purification strategies of aspartic proteinases from Mucorales.…”
Section: Recovery and Purification Of Mucor Spp Aspartic Proteinasesmentioning
confidence: 99%
“…This concept has been proven experimentally: the R. pusillus enzyme retains 71% of its original activity when heated for 10 min at 55°C while, under similar conditions, the calf rennet and the M. bacilliformis aspartic proteinase retain 31% and 10% of the initial milk-clotting activity, respectively (Fraile et al 1981). Fernandez-Lahore et al (1999) have shown that a M. circinelloides strain (M-105) produces a wild-type enzyme with very promising characteristics, being even less heat stable than the enzyme obtained from M. bacilliformis cultures.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Acidic proteases have been isolated from various species of Aspergillus (O'Donnell et al, 2001;Tremacoldi et al, 2004), Mucor (Escobar and Barnett, 1993;Fernandez-Lahore et al, 1999) and Rhizopus (Kumar et al, 2005). Fu et al (2008) obtained an acid protease from Bacillus megaterium KLP-98 which had an optimum pH of 5.5 and was stable in the pH range of 4.5 -6.0.…”
Section: Effect Of Ph On Protease Activitymentioning
confidence: 99%